Marine Algae Collected during the Scientific Expedition to Bachok, Kelantan and the Islands of Terengganu with One New Record, Pterocladiella for Malaysia - Phang, Siew-Moi; Lim, Phaik-Eem; Yeong, Hui-Yin; Ng, Woan-Shien; Song, SzeLooi (Malaysian Journal of Science, 2010)
In 2008, a scientific expedition to Bachok (the new Marine Station), Kelantan and the vicinity of Terengganu, was organised by the Institute of Ocean and Earth Sciences (IOES), University of Malaya. The objective of the expedition was to collect and document the natural resources of Bachok and its vicinity. Our team collected and identified the marine algae resources of the area. A total of 133 taxa of marine algae and four taxa of seagrasses were compiled from the results as well as previous records for Kelantan and Terengganu. The marine algae comprise 3 families of Cyanophyta with 4 genera and 4 taxa; 10 families of Chlorophyta with 13 genera and 35 taxa; 16 families of Rhodophyta with 38 genera and 63 taxa; 4 families of Phaeophyta with 8 genera and 31 taxa. Only 35 taxa were collected during this present survey, the most from the Rhodophyta (14 taxa) followed by the Phaeophyta (12 taxa), the Chlorophyta (8 taxa) and the Cyanophyta (4 taxa). Of these, the Cyanophyta Lyngbya, Oscillatoria, Microcoleus and Brachytrichia; the Chlorophyta Ulva compressa, Ulva flexuosa, Ulva intestinalis, Caulerpa serrulata var. boryana; the Rhodophyta Gelidiella acerosa, Gelidium pusillum, Actinotrichia fragilis, Acanthophora spicifera; and the Phaeophyta Dictyota ciliolata, Lobophora variegata, Padina antillarum, Hormophysa cuneiformis and Turbinaria conoides are new records for Kelantan and Terengganu. The Rhodophyta Pterocladiella is a new record for Malaysia. Two families of seagrasses with 3 genera and 4 taxa were collected and included in this checklist. A new species of Halophila will be studied further